Isolation and characterization of cellulose degrading bacteria from Sago pith waste - Shamsyah, Binti Hamid. (Universiti Malaysia Sarawak (UNIMAS), 2006)
Sago pith waste is one of the most abundant recyclable waste materials in our country. In this research, the most active cellulose degrading bacteria from sago pith waste was isolated and studied. Morphological characterization includes gram staining and some biochemical tests presumed the bacteria are pertained in genera Staphylococcus. For molecular characterization, genomic DNA was extracted from the bacteria and amplified by polymerase chain reaction before being sequenced. However, sequencing result failed to detennine the specific species of the isolate. Crude cellulase enzymes was produced from the bacteria and assayed for its relative activity in different temperature, time and pH. Enzyme activities were expressed as units per milliliter (U/ml), where I U was defined as I milimol of substrate oxidized per minute. The crude enzyme displayed highest activity in incubation at 30°C and is stable up to 60 to 80°C of temperature but with 50 to 80% decrease of activity. The optimal time for its activity is 8 minute while optimal pH is 7.0. Further research on the bacteria isolated and its cellulase enzymes produced should be conducted due to its potential in biotechnological applications and commercialization.